2006
DOI: 10.1063/1.2335362
|View full text |Cite
|
Sign up to set email alerts
|

Melt dispersion mechanism for fast reaction of nanothermites

Abstract: An unexpected mechanism for fast oxidation of Al nanoparticles covered by a thin oxide shell (OS) is proposed. The volume change due to melting of Al induces pressures of 0.1–4GPa and causes spallation of the OS. A subsequent unloading wave creates high tensile pressures resulting in dispersion of liquid Al clusters, oxidation of which is not limited by diffusion (in contrast to traditional mechanisms). Physical parameters controlling this process are determined. Methods to promote this melt dispersion mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
177
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(184 citation statements)
references
References 12 publications
6
177
0
1
Order By: Relevance
“…While some studies suggested that it was a fixed value around the melting temperature of the aluminum particles [21,24], many others suggest that the ignition temperature is not a material property but depends upon the environmental variables, such as the heating rates [25][26][27], particle size [28], specific experimental conditions or methods employed [29,30] and instruments used [29,31,32]. It is still debatable if the ignition of aluminum nanoparticles occurred before or after the melting temperature of aluminum.…”
Section: Influence Of the Heating Ratementioning
confidence: 99%
“…While some studies suggested that it was a fixed value around the melting temperature of the aluminum particles [21,24], many others suggest that the ignition temperature is not a material property but depends upon the environmental variables, such as the heating rates [25][26][27], particle size [28], specific experimental conditions or methods employed [29,30] and instruments used [29,31,32]. It is still debatable if the ignition of aluminum nanoparticles occurred before or after the melting temperature of aluminum.…”
Section: Influence Of the Heating Ratementioning
confidence: 99%
“…For pure nAl, it has been suggested that the early ignition was associated with the melting and solid phase transition of alumina [30,35]. Under very high heating rates (i.e, >10 3 K/s), the melting of aluminium would fragmentize the shell and led to a global combustion event [36]. From the DSC/TGA data and the identified first-stage reaction, Eq.…”
Section: Thermal Analysis and Reaction Kineticsmentioning
confidence: 99%
“…This passivation shell can become an appreciable portion of the total material when the particle size approaches nanometer dimensions [16]. Levitas et al [21] proposed the following mechanism to explain the fast oxidation of Al nanoparticles. The thin oxide skins on the outside of the particles represent rigid pressure vessel walls.…”
Section: Introductionmentioning
confidence: 99%